(untitled) (Fiep Bulletin - online, 2011)
The objective of the present work is to analyse questions related to the State Council of Sports and Leasure of Espirito Santo. This work refers to a qualitative documental research that focuses on references such as the State regiment and legislation on the State Council of Sports and Leasure. It evaluates categories: composition, character and attributes of this department and concludes that disparities exist between the composition of governmental members and the representation of society in the investigated context of the State Council of Sports and Leasure. Furthermore, it is verified that this authority does not have deliberative character, fact that may invibialize the proposition and formulation of public politics in this field.